FOOTPRINT AND DIRECT IMPACT OF ANTHROPOGENIC ACTIVITIES ON GROUNDWATERS FROM MEDIAS AREA - HOAGHIA, Maria-Alexandra; ROMAN, Cecilia; LEVEI, Erika Andrea; RISTOIU, Dumitru (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Groundwater represents an important and direct source of fresh water, vulnerable to contamination. Groundwater composition is easily influenced by anthropogenic activities. Lack of sewerage facilities impress direct footprint on groundwater composition. Nitrogen compounds (NO2-, NO3-, NH4+), SO42-, K+, Cl-, Mg2+, Ca2+, Na+, pH and total dissolved solids were analysed from seven well waters from Medias area. The results showed the seasonal variation of analysed parameters, the nitrogen compounds, K+ and Ca2+ exceeding the maximum admissible concentration in the majority of samples. The Stiff and Piper diagrams confirmed that the studied waters are Ca-HCO3 type and have the same sources.